Building climate resilience: awareness of climate change adaptation in German outpatient medical practices - Nicola Alexandra Litke; Regina Poß-Doering; Valeska Fehrer; Martina Köppen; Stephanie Kümmel; Joachim Szecsenyi; Michel Wensing (BMC, 2024)
Abstract Background Climate change is seen as the biggest health threat of the twenty-first century. Making outpatient medical practices resilient is therefore crucial to protect vulnerable groups and maintain quality of care. Awareness is a precondition for action. This study aims to explore awareness (knowledge, experience and attention) of climate change adaptation among stakeholders of outpatient medical practices. Methods Semi-structured interviews and focus groups with stakeholders of outpatient medical practices were conducted. The qualitative data were analysed in a two-step Thematic Analysis process. Results In total, n = 40 stakeholders participated in two focus groups and 26 interviews. The findings show a mixed degree of awareness in outpatient medical practices. The spectrum ranged from a passive role with curative acting only, handing over responsibility to others and a low perceived self-efficacy to a proactive and responsible implementation of adaptation strategies. Participants who saw the need and responsibility of climate change adaptation in medical practices perceived low additional workload. In general, implementation of climate change adaptation measures and general awareness of climate change adaptation appeared to be depending on a certain tension for change and a higher self-efficacy. Conclusion Medical practices, and specifically primary care, plays a crucial role in climate change adaptation, and awareness needs to be increased further in order to cope with consequences of climate change. To facilitate this, there should be a strong emphasis on climate change adaptation strategies being part of outpatient care provider roles rather than being perceived as an "add-on" to already high workloads.